Critical Analysis on Business Innovation for Traders During Pandemic Covid-19: An Islamic Economics Perspective - Maman Surahman; Popon Srisusilawati; Redi Hadiyanto; Tri Ambarwati; Reyhan Maharis Fadilah (Falah: Jurnal Ekonomi Syariah, 2022)
This study aims to analyze business innovation in Islam Economics to the sustainability of traders around UNISBA during pandemic Covid-19. This study was qualitative using descriptive analytical approach. Type of data collected was primary data obtained from interview. The data analysis technique used was descriptive model qualitative in shape data collection, data reduction, data display, and conclusion. The result found that traders can continue their business by using e-marketing and online marketplace which considered necessary to be implemented, especially in the Covid-19 pandemic situation. The contribution of this research to enhance the development of science and business practice in the implementation of e-marketing dan online marketplace.